The Effect of Egg Weight on Hatching Power and Hatching Weight of Super Javanese (Joper) Chickens - Gayuh Syaikhullah; Reikha Rahmasari; Budi Prasetyo (Musamus Journal of Livestock Science, 2023)
This research aims to determine the relationship between egg weight and fertility, hatching loss, hatchability, and fixed weight of Super Javanese chickens (Joper) in the context of developing the TEFA (teaching factory) Breeding and Hatchery at the Politeknik Negeri Jember. This research used 40 layer hens and 5 rooster Bangkok chickens reared in colonies with a ratio of 8:1. Treatment consisted of grouping egg weights, namely P1 (<55 g) and P2 (>55 g). Observations were made three times during the hatching period. The variables observed were fertilization, hatchability, and hatching weight. The data obtained was analyzed descriptively and analytically. The results showed that egg weight was closely correlated with hatching weight (R = 0.98) and had a regression value of Y = -0.625 + 0.686X. The hatching weight of eggs weighing <55 g and eggs weighing >55 g had a significant difference (P<0.05) with eggs weighing >55 g having a greater hatching weight. Egg weight had no significant effect (P>0.05) on hatchability or the percentage of hatched or unhatched eggs. The conclusion that can be drawn is that egg weight has a real influence and is closely correlated with hatching weight (DOC weight).